Peran Penggunaan Bahasa Isyarat Sejak Dini pada Perkembangan Emosi Anak Tuli di The Little Hijabi Homeschooling - Aisyah Andini Rahmalia; Luqman Hidayat; Faiz Noormiyanto (EduInovasi: Journal of Basic Educational Studies, 2025)
Deaf children often face challenges in emotional development due to communication barriers, which may lead to frustration and tantrum behaviors. This study aims to determine the role of early sign language use in the emotional development of Deaf children at The Little Hijabi Homeschooling. The research is expected to provide an in-depth understanding of how sign language serves as a medium for emotional regulation and supports the psychosocial development of Deaf children. This research employed a qualitative method within the framework of social constructivism. Data were collected through passive participatory observation, interviews with parents and teachers, and documentation at The Little Hijabi Homeschooling. The collected data were analyzed through data reduction, data presentation, and conclusion drawing. Data validity was ensured using source triangulation and technique triangulation to confirm the accuracy of the findings. The results show that the early use of sign language plays a crucial role in the emotional development of Deaf children. Sign language serves as a foundation for children to express and manage emotions effectively, thereby reducing the frequency of tantrums and negative behaviors. Furthermore, communication skills through sign language were found to enhance children’s self-confidence and social engagement, helping them overcome feelings of inferiority and develop a sense of competence aligned with their developmental stage.